Perencanaan Tenaga Pendidik dan Kependidikan di Universitas Darunnajah - Nesa Novrizal; Rizka Fajrina S; Maemunah Sa'diyah (JPG: Jurnal Pendidikan Guru, 2024)
Planning for lecture and education staff is one of the essential factors in managing human resources in university. One of the success factors of an education does not escape the performance of a lecture and education staff. This research aims to find out how the planning of lecture and education staff at Darunnajah University, a private university born from Darunnajah Jakarta Islamic boarding school. This research uses a qualitative approach with a triangulation method, which combines primary and secondary data from various sources. Primary data was obtained from in-depth interviews with several key informants involved in its preparation. Secondary data was obtained from official documents, such as the Statute, strategic plan, and HR guidelines. The results showed that the planning of teaching and education personnel at Darunnajah University is carried out systematically and integrated with the university's long-term and short-term plans. The planning of lecture and education staff at Darunnajah University is based on the analysis of needs, availability, lecture and education staff Factors that influence this planning include the vision and mission of the university, government policies, the development of science and technology, and the competence of teaching and education personnel. This planning also pays attention to qualitative aspects, such as qualifications, competencies, performance, and the welfare of teaching and education personnel.